Surface nitriding and alloying of steels with Ti and Nb atoms by compression plasma flows treatment - Cherenda N. N. Nikolay Nikolaevich; Uglov V. V. Vladimir Vasilievich; Kuleshov A. K. Aleksandr Kuzmich; Astashinsky V. M. Valentin Mironovich; Kuzmitsky A. S. Anton Mikhaylovich (2016, 2016)
Title screen